The Role of Prisons in Providing Skills to Prisoners as an Effort to Prevent Repetition of Criminal Offenses - Yoseph Natiur Lumban Raja; Herlina Manullang; Melihertati Gultom (Sultan Agung Notary Law Review, 2026)
Vocational skills in correctional institutions (Lapas) are a crucial instrument in the Indonesian correctional system, as mandated by Law No. 22 of 2022 concerning Corrections which replaces Law No. 12 of 1995. This program is designed to equip correctional inmates (WBP), especially prisoners, with practical skills in engineering, handicrafts, and laundry, in order to facilitate social reintegration, economic independence, and prevention of recidivism through holistic rehabilitation. The complex background of prison dynamics including overcapacity in Tebing Tinggi Class IIB Prison, psychological pressure, and negative labeling of the community is exacerbated by the sharp difference between life inside and outside prison, thus threatening the goal of correctional based on the principles of protection, humanity, and mutual cooperation.